Special Educational Needs, Distance Learning, Inclusion and COVID-19 - Donatella Rita Petretto; Ilaria Masala; Carmelo Masala (MDPI AG, 2020)
In the last two months, school closure has been one of the more used worldwide "not-pharmacological mitigation strategies" to prevent and limit infection from COVID-19, and to delay the outbreak's peak [...]